Excellent energy storage performance and thermal property of polymer-based composite induced by multifunctional one-dimensional nanofibers oriented in-plane direction. (February 2019) - Zhang, Yue; Zhang, Changhai; Feng, Yu; Zhang, Tiandong; Chen, Qingguo; Chi, Qingguo; Liu, Lizhu; Li, Guofeng; Cui, Yang; Wang, Xuan; Dang, Zhimin; Lei, Qingquan
Abstract: As advanced dielectric materials for the applications in electronics and electrical power systems with the ever-increasing requirements, the polymer-based dielectric nano-composites are brilliantly emerging. However, there are long standing challenges of the unsatisfactory electric breakdown strength and the heat accumulation induced by dielectric loss of composite. In this study, we propose an artificial nano-composite with excellent comprehensive performance by controlling the orientation of one-dimensional (1D) 0.5Ba(Zr0.2 Ti0.8 )O3 -0.5(Ba0.7 Ca0.3 )TiO3 nanofibers (BZCT NFs) and adjusting the interaction between BZCT NFs and poly(vinylidene fluoride) (PVDF) matrix via SiO2 buffer layer. Remarkably, PVDF nano-composite with only 3 vol% aligned BZCT NFs coated by SiO2 (BZCT@SiO2 NFs, 3 vol% Aligned BZCT@SiO2 -PVDF) possesses an impressive energy storage performance, including the superior Weibull characteristic breakdown strength ( E b ) of 576 kV/mm and the ultrahigh discharged energy density ( U e ) of 18.9 J/cm 3 . Meanwhile, the temperature distribution in this typical composite is more homogeneous according to the test and simulation results. This demonstrated work not only opens a new door to preparing an excellent performance of polymer-based dielectric nano-composites, but also points out a route to the industrialization of energy storage dielectrics. Graphical abstract: The 3 vol% aligned BZCT@SiO2 -PVDF nanocomposite with an excellent performance in terms of energy storage and thermal properties has been obtained by introduction of the aligned core-shell BZCT@SiO2 nanofibers. Highlights: The core-shell structure of BZCT@SiO2 nanofibers have been designed. Large-aspect-ratio BZCT NFs contribute to dielectric property of the composite. SiO2 shell is beneficial to enhance the breakdown strength of the composite. Thermal conductivity is improved by the aligned one-dimensional nanofibers.